MANAJEMEN TENAGA KERJA TEMPAT PELELANGAN IKAN (TPI) AERTEMBAGA KOTA BITUNG - Lengkong, Amelia; Dien, Christian R.; Aling, Djuwita R.R (Universitas Sam Ratulangi, 2013)
Abstract The purpose of this research is to study labour management at the fish auction place Aertembaga Bitung city. The research was conducted at the office of the Regional Technical Implementation Unit / Fish Auction Aertembaga, Bitung City. The data obtained was analyzed using descriptive analysis method, which analyzes the data through a depiction of what the results of their research. Organizational structure in UPTD/TPI indicates that the process of division of labour can be divided broadly upright (vertical) and the horizontal line (horizontal). In this case is the Head of the Department of Marine and Fisheries and the head UPTD / TPI. While the horizontal division of labour based on the specificity of horizontal work based on the specificity of the work that is sub section administration, data collection sexy Fish (sub-section of facilities/infrastructure, marine and sub â€‹â€‹sections of facilities/infrastructure land). At this time in the labour UPTD/TPI totalling 5 people. The main duties and functions of the head UPTD/TPI are as follows: coordination functions for all existing activities. Each section or sub-section, it will directly accountabel for the results of their work through written reports each month or as requested by the Head of the Department of Marine and Fisheries. Keywords: fish auction, management, labour, duties and functions. Â Abstrak Tujuan dari penelitian ini adalah mempelajari manajemen tenaga kerja di Tempat Pelelangan Ikan Aertembaga Kota Bitung. Penelitian ini dilaksanakan di kantor Unit Pelaksana Teknis Daerah/Tempat Pelelangan Ikan Aertembaga, Kota Bitung. Data yang diperoleh kemudian dianalisis dengan menggunakan metode analisis deskriptif, yaitu menganalisis data-data hasil penelitian melalui penggambaran apa adanya. Struktur organisasi di UPTD/TPI menunjukkan proses pembagian kerja yang dapat dibagi-bagi secara garis tegak (vertikal) maupun pada garis mendatar (horizontal). Dalam hal ini adalah Kepala Dinas Kelautan dan Perikanan dan Kepala UPTD/TPI. Sedangakan pembagian kerja secara horizontal didasarkan atas spesialisasi kerja secara horizontal didasarkan atas spesialisi kerja yaitu Sub Bagian Tata Usaha, seksi Pendataan Ikan (sub seksi sarana/prasarana laut dan sub seksi sarana/prasarana darat). Pada saat ini tenaga kerja di UPTD/TPI berjumlah 5 orang. Adapun tupoksi dari kepala UPTD/TPI adalah sebagai berikut : menjalankan fungsi koordinasi untuk semua kegiatan yang ada di masing-masing seksi maupun sub seksi dan secara langsung akan mempertanggungjawabkan hasil pekerjaannya melalui laporan tertulis tiap bulan atau sesuai dengan permintaan kepada Kepala Dinas Kelautan dan Perikanan. Kata Kunci:pelelangan ikan, manajemen, tenaga kerja, tugas pokok dan fungsi